Digital transformation in waste management: Enhancing financial transaction efficiency at a waste bank (University of Merdeka Malang, 2024)
Waste management poses a serious global challenge. Indonesia, as one of the world's largest waste producers, faces significant impacts from this issue. At Bank Sampah Pamulang 25, manual transaction recording has been a major problem leading to various difficulties and data inaccuracies. To address this, the Community Partnership Program (PKM) was implemented focusing on developing the Waste Bank Financial Information System (SIKEBAS) to enhance efficiency and productivity. The research method used was Community-Based Participatory Research (CBPR), involving collaboration between local communities, students, and lecturers. Through a series of activities, the SIKEBAS website was successfully developed to automate waste and financial data recording and management. Evaluation of the implementation results showed a significant improvement in efficiency and productivity among Bank Sampah Pamulang 25 staff. Initially, 88.9Â percent of participants did not understand the use of technology in transaction recording at the waste bank. However, after socialization, 75Â percent of participants strongly agreed and 25Â percent agreed that the SIKEBAS website facilitated the transaction process. Thus, the development of the web-based information system SIKEBAS has proven to be an effective solution to address the challenges of manual waste management.